Contact angle for theoretical parameterization of immersion freezing rate inferred from the freezing temperature - Jun-Jie Chang; Jen-Ping Chen; Pei-Hsin Liu (Terrestrial, Atmospheric and Oceanic Sciences)
Abstract This study derived contact angles for fifteen types of pollens, nine types of fungi, ten types of bacteria, one type of diatom, and twelve types of mineral dust for use in the parameterization of immersion freezing based on the classical nucleation theory (CNT). Our approach is to interpret freezing temperature measurement results with the stochastic nucleation concept. In this way, the abundant freezing temperature data available in the literature can be converted to contact angles that needed in the CNT parameterization for a variety of INPs. The derived contact angles compared well with values independently obtained in earlier studies based on a pure-CNT approach using laboratory nucleation rate data. The uncertainties in contact angle calculation associated with the definition of onset nucleation rate, the activation energy, and the ice-nuclei size are estimated to be about ± 1–2°, ± 1–5°, and ± 1–2°, respectively, among different ice-nucleating particles.